2021
DOI: 10.3389/fchem.2020.621925
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Time-Resolved Fluorescence Immunoassay for Quantitative Determination of Oxyfluorfen in Food and Environmental Samples

Abstract: The direct and indirect competition time-resolved fluorescence immunoassays (dc-TRFIA, ic-TRFIA) were established by combining the autofluorescence properties of lanthanide europium (Eu) with the monoclonal antibody of oxyfluorfen. The purified Eu antibody was optimized and the conditions such as the working concentration of the Eu antibody, monoclonal antibody, and working buffer were optimized. In the optimal condition, the IC50 of dc-TRFIA was 10.27 ng/mL, the lowest detection limit IC10 was 0.071 ng/mL, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In this study, we established an indirect competition TRFIA for OA in shellfish. Goat anti-mouse IgG, i.e., secondary antibody, was labeled with europium for low detection limit and high sensitivity (Esteve-Turrillas et al, 2010;Sesay et al, 2013;Li et al, 2014;Sheng et al, 2020). Compared with labeling the primary antibody, labeling the secondary antibody avoids the interference of the marker to the binding site of the antigen on the first antibody.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we established an indirect competition TRFIA for OA in shellfish. Goat anti-mouse IgG, i.e., secondary antibody, was labeled with europium for low detection limit and high sensitivity (Esteve-Turrillas et al, 2010;Sesay et al, 2013;Li et al, 2014;Sheng et al, 2020). Compared with labeling the primary antibody, labeling the secondary antibody avoids the interference of the marker to the binding site of the antigen on the first antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Rareearth metal ions, Eu 3+ and Sm 3+ , are used as labels because of their characteristics of high fluorescence intensity, ability to overcome high-background absorption, and long relaxation time (Wang et al, 2009;Huang et al, 2009;Zhang et al, 2011). TRFIA has been used for the detection of small molecules, such as salbutamol in the environment, aflatoxin b1 in feed, and oxyfluorfen in food, and has demonstrated excellent sensitivity and accuracy (Hu et al, 2018;Fang et al, 2019;Sheng et al, 2020). In this study, an OA detection method was developed using TRFIA on the basis of competitive immunization and applied this TRFIA method on shellfish.…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al established time-resolved fluorescence microspheres (TRFMs) for the detection of hydrochlorothiazide, and the limit of detection (LOD) was 1/14 lower than the liquid chromatography-tandem mass spectrometry method. Besides, the TRF materials were also extensively used in medical diagnosis and the detection of food contaminants, such as biotoxins, pathogenic microorganisms, pesticides, heavy metal ions, biomarkers, etc. Recently, several researchers indicated that compared with ELISA, the sensitivity of the TRF immunosensor was greatly improved by 1–2 orders of magnitude and the measuring time was significantly reduced by more than 50%. , Moreover, TRF sensors can be effectively operated to increase the signal-to-background ratio with their special fluorescence properties. , …”
Section: Introductionmentioning
confidence: 99%
“…CLIA is a highly sensitive detection method, but it uses chemiluminescent substances as markers, which leads to defects such as high background values, poor stability, and low reproducibility (Zhang et al, 2018;Xiao and Xu, 2020). As a typical commercialized product, ELISA has the advantage of high stability and good repeatability, while elaborate preprocessing and washing steps lead to the strict requirement for professional operators (Zhao et al, 2019;Sheng et al, 2021). Therefore, there is an urgent need for a low background, high-throughput, and easy-to-operate system to achieve rapid, sensitive, and accurate analysis of targets.…”
Section: Introductionmentioning
confidence: 99%